Situational analysis of occupational safety, health, and dignity of sanitation workers: : a case of Mukuru kwa Reuben Slums, Nairobi, Kenya - Ngatia, Alex Mutahi; Anciano, Fiona; Kagendo, Dorothy; Riungu, Joy (African Journal of Science, Technology and Social Sciences, 2024)
The safety, health, and dignity of sanitation workers, despite being critical to global sanitation efforts, have long been neglected. This study sought to assess the occupational hazards faced by sanitation workers in informal settlements as well as examining factors associated with the state of occupational safety, health, and dignity of the informal settlement sanitation workers. The study adopted a mixed-methods approach, combining qualitative and quantitative data to provide a holistic understanding of the issues. It employed a case study method to explore the specific challenges faced by sanitation workers in Mukuru slums, considering socioeconomic, environmental, cultural, and policy factors. A sample of 40 sanitation workers was selected for the study based on purposive snowballing technique. Data collection was by use of semi-structured questionnaires, observation, and interviews. The findings revealed significant occupational hazards faced by sanitation workers, including chemical exposure, psychosocial challenges, physical injuries, and biological risks. Socioeconomic factors such as low income and limited education contributed to the workers' vulnerability, while social stigma and discrimination negatively impacted their dignity. Based on the research findings, several recommendations are proposed. These include enhancing training and awareness programs, providing access to personal protective equipment, improving working conditions.